Target-specific requirements for enhancers of decapping in miRNA-mediated gene silencing. - Eulalio, A; Rehwinkel, J; Stricker, M; Huntzinger, E; Yang, S; Doerks, T; Dorner, S; Bork, P; Boutros, M; Izaurralde, E (2007)
microRNAs (miRNAs) silence gene expression by suppressing protein production and/or by promoting mRNA decay. To elucidate how silencing is accomplished, we screened an RNA interference library for suppressors of miRNA-mediated regulation in Drosophila melanogaster cells. In addition to proteins known to be required for miRNA biogenesis and function (i.e., Drosha, Pasha, Dicer-1, AGO1, and GW182), the screen identified the decapping activator Ge-1 as being required for silencing by miRNAs. Depleting Ge-1 alone and/or in combination with other decapping activators (e.g., DCP1, EDC3, HPat, or Me31B) suppresses silencing of several miRNA targets, indicating that miRNAs elicit mRNA decapping. A comparison of gene expression profiles in cells depleted of AGO1 or of individual decapping activators shows that approximately 15% of AGO1-targets are also regulated by Ge-1, DCP1, and HPat, whereas 5% are dependent on EDC3 and LSm1-7. These percentages are underestimated because decapping activators are partially redundant. Furthermore, in the absence of active translation, some miRNA targets are stabilized, whereas others continue to be degraded in a miRNA-dependent manner. These findings suggest that miRNAs mediate post-transcriptional gene silencing by more than one mechanism.